PENANAMAN NILAI-NILAI AKHLAK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MENGHADAPI ERA MILENIALDI SMA NEGERI 2 REJANG LEBONG - Ririn Eka Monicha; Lukman Asha; Asri Karolina; Eka Yanuarti; Maryamah Maryamah; Mardeli Mardeli; Nyayu Soraya (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
The cultivation of moral values ​​in Islamic Education learning becomes an effort in facing various challenges in this millennial era. The purpose of strengthening moral values ​​is to guide and foster students to be better persons and be able to have good morals, which are in accordance with Islamic values. As regards moral values, the role of educators in cultivating moral values ​​is very crucial. It is to prepare students’ positive attitude to face the millennial era. There are several supporting factors in cultivating students’ moral values ​​in SMA 2 Rejang Lebong. They are the existence of support and collaboration from the school, cooperation between teachers and parents, and the fulfillment of the school’s facilities and infrastructure. On the other hand, there are some factors that obstruct the cultivation of moral values that are influenced by the students’ selves and peer relations. This research is qualitative research, qualitative research aims to examine the conditions of natural objects and emphasize understanding the in-depth meaning of a symptom. Data were collected through interviews (direct and indirect), observation, and documentation. The purpose of this study is to find out how to instill moral values ​​in learning Islamic religious education to face the millennial era and to determine the supporting and inhibiting factors for planting moral values ​​in learning Islamic religious education facing the millennial era in SMA Negeri 2 Rejang Lebong.